The Agricultural mechanization and its impact on agricultural development of Ecuador - Intriago Mendoza, Fernando Rodolfo (SATHIRI, 2019)
Ecuador, like many countries that are underdeveloped, must seek alternatives that contribute to generate wealth, which favors the progress and development of the country. Within the alternatives, agriculture is seen as a preponderant factor in achieving this goal. Our country is privileged by the different climatic zones it has, which makes it possible to cultivate and produce a great variety of agricultural products. Technology has advanced in a global way in many areas, including agronomy; In Ecuador, agriculture has been developing for a long time, but this advance has not been able tobe evidenced in the way it should be. It is important to indicate the great advantages that we can obtain when using these technologies in the different stages of production, either in plants or in animals, which greatly favor the strengthening of the productive matrix and the long-awaited dream of national development.